Group 1 and group 2 hemagglutinin stalk antibody response according to age - Sánchez-de Prada, Laura; Sanz-Muñoz, Iván; Sun, Weina; Palese, Peter; Ortiz de Lejarazu, Raúl; Eiros, José María; García-Sastre, Adolfo; Aydillo, Teresa (Frontiers in Immunology, 2023)
Objective: Antibodies elicited by seasonal Influenza vaccines mainly target the head of the hemagglutinin (HA). However, antibodies against the stalk domain are cross-reactive and have proven to play a role in reducing influenza disease severity. We investigated the induction of HA stalk-specific antibodies after seasonal influenza vaccination taking into account the age of the cohorts. Methods: A total of 166 individuals were recruited during the 2018 influenza vaccine campaign (IVC) and divided in groups: <50(n=14), 50-64(n=34), 65-79(n=61) and ≥ 80 (n=57) years old. Stalk specific antibodies were quantified by ELISA at day 0 and day 28 using recombinant viruses (cH6/1 and cH14/3) containing an HA head domain (H6 or H14) from wild bird origin with a stalk domain from human H1 or H3, respectively. The Geometric mean titer (GMT) and the Fold rise (GMFR) were calculated, and differences assessed using ANOVA adjusted by the False Discovery Rate (FDR) and the Wilcoxon tests (p<0.05). Results: All age groups elicited some levels of increase of anti-stalk antibodies after receiving the influenza vaccine except for ≥ 80-year-old cohort. Additionally, < 65-year-old vaccinees had higher group 1 antibody titers versus group 2 before and after vaccination. Similarly, vaccinees within the <50-year-old showed higher increase of anti-stalk antibody titers when compared to older individuals (≥ 80 years old), especially for group 1 anti-stalk antibodies. Conclusion: Seasonal influenza vaccine can induce cross-reactive anti-stalk antibodies against group 1 and group 2 HAs. However, levels of induction were in general low, especially in the oldest groups.